A Rare Case of Bilateral Posterior Tibial Artery Aneurysm Presenting as Unilateral Acute Limb Ischemia - Andrew T. Hattam; Mayur Krishnaswamy (Case Reports in Vascular Medicine)
True aneurysms of the tibial arteries are extremely rare. Of the few previously described tibial artery aneurysms, there are scant reports of isolated true aneurysms of the posterior tibial artery (PTA). In this report, we describe the second documented case of bilateral true PTA aneurysms. Unique aspects of this case are that the aneurysmal PTA were the only patent tibial arteries bilaterally, the aneurysms were degenerative in nature, and initial patient presentation was due to aneurysm thrombosis causing acute foot ischemia. The clinical and radiological features of this case, as well as surgical decision making and management, are discussed.